Solid holdup in liquid solid circulating fluidized bed with viscous liquid medium - Gnanasundaram, N.; Loganathan, M.; Perumal, Kumar (Elsevier, 2014)
© 2014 Production and hosting by Elsevier B.V. Average solid holdup in the axial direction was investigated in a liquid solid circulating fluidized bed riser (LSCFB), with liquids of different viscosities. The effect of operating parameters including; primary, secondary and total velocity, particle diameter and density was studied. Experiments were conducted using water and glycerol at different concentration having viscosities in the range 1-1.36 cp. The results indicated that the solid holdup in the riser was axially uniform for viscous liquids and increases with increase in auxiliary velocity. The average solid holdup decreases with increase in total velocity and increases with increase in viscosity for sand-glycerol, glass bead-glycerol system. The experimental measurements were compared with the existing holdup model prediction that varied linearly with viscosity. Further, a correlation was developed to estimate average solid holdup in the riser, and the performance of the expression was compared with the present experimental data.